The Structure of the Soviet economy : analysis and reconstruction of the 1966 input-output table - Treml, Vladimir G.; Gallik, Dimitri M.; Kostinsky, Barry L.; Kruger, Kurt W. (New York, Praeger Publishers, 1972)
This book talking about the rapid increase flow of soviet imput-output and related data of great analytical importance both for soviet economists and statisticians and for western students of soviet economics.
Bibliography: p. [639]-655.
aia 28/01/2019
Loans
Keywords: Industries; Input-output tables; Economic conditions